Impact Evaluation of Youth-Friendly Family Planning Services in Uganda - Asingwire, Narathius; Muhangi, Denis; Kyomuhendo, Swizen; Leight, Jessica (International initiative for impact evaluation, 2019)
This final impact evaluation grantee report has been submitted in partial fulfilment of the requirements of grant UPW.06 awarded under the Uganda Policy Window. 3ie is making it available to the public in this final report version as it was received. The encouragement design in the study did not lead to an increased uptake of the programme and therefore the identification strategy failed.